The dynamics of individual male earnings in Great Britain: 1991-1999 - Xavier Ramos (University of Essex, Institute for Social and Economic Research (ISER), 2001)
In this paper I analyse the dynamic structure of earnings in Great Britain for the period 1991-1999 by decomposing the earnings covariance structure into its permanent and transitory components. Using information on monthly earnings of male full-time employees from the first nine waves of the British Household Panel Study I find that earnings inequality increases over the Nineties. However, earnings mobility may have also increased. That is, for this period earnings persistence falls. Surprisingly, I also find that relative earnings persistence declines over the life cycle, which implies lower mobility for younger cohorts. This evidence is at odds with previous literature on earnings dynamics both for Britain and other OECD countries. Unlike recent studies, I also consider the effects of observed characteristics on the covariance structure of log earnings and find that human capital and job related characteristics account for nearly all persistent earnings differences and that the transitory component is highly persistent.
Keywords: 330